Epithelioid sarcoma presenting as the reflex sympathetic dystrophy syndrome. Issue 737 (March 1987) - Summers, C. L.; Shahi, M.
Abstract : A case of reflex sympathetic dystrophy caused by an epithelioid sarcoma is presented. This is the first report of a local peripheral tumour associated with the reflex sympathetic dystrophy syndrome.